Fundamentals of plant pathology - Mehrotra R S
This book is unique as it contains parts on general concepts as well as parts on specific diseases, that is in the beginning from chapters 1 to 10 discuss the host-pathogen interaction in detail; and in the later chapter, authors give an account of diseases caused by fungi, bacteria, phytoplasma, viruses, and nematodes. In each chapter (chapter 13 to 24), major diseases are discussed in detail, and minor diseses are given in a tabular from.